Magical Imaginations : Instrumental Aesthetics in the English Renaissance - Guenther, Genevieve Juliette (Book collections on Project MUSE., 2012)
"Through analyses of texts ranging from sermons and theological treatises to medical tracts and legal documents, Genevieve Guenther sheds new light on magic as a cultural practice in early modern England. She demonstrates that magic was a highly pragmatic, even cynical endeavor infiltrating unexpected spheres--including Elizabethan taxation policy and Jacobean political philosophy. With this new understanding of early modern magic, and a fresh context for compelling readings of classic literary works, Magical Imaginations reveals the central importance of magic to English literary history"--Pub. desc.